What’s age got to do with it? Accounting for individual factors in second language accent - Moyer, Alene (Studies in Second Language Learning and Teaching, 2014)
Empirical research conducted over the past few decades suggests that the age at which an individual is first exposed to a second language affects long-term outcomes, in particular for phonology. The question that has occupied scholars of various bents is what, exactly, underlies the robust age effects observed. Does age imply immutable changes in one’s ability to ever sound native-like? Are these changes neurological, cognitive, or socio-psychological in nature? What role do L2 use and contact play? Do age-related influences apply to all individuals, or can language learners actually chart their own course when it comes to accent? This paper will outline basic assumptions of the critical period for phonology while suggesting a different approach to the age question that highlights the individual’s role in both process and outcome. Constructs such as L2 experience, motivation, self-concept, learning approach, and willingness to communicate are discussed in depth in order to show the fundamental connection between cognition and affect so critical for late phonological learning. A re-orientation of the age research is suggested as a result, to prioritize contextual understandings of language use and learner agency.